Antioxidant Studies on Aqueous and Organic Extracts of Terminalia bellerica Roxb. Bark - Sherin, L.; Shujaat, S.; Nazir, R. (Asian Journal of Chemistry, 2011)
Traditional Ayurvedic plant, Terminalia bellerica Roxb. (TB), has been widely used for thein vitro antioxidant activities of aqueous and organic extractsTerminalia bellerica Roxb. bark were evaluated50 = 1.00 μg/mL) and ethyl acetate (IC50 = 1.54 μg/mL) extracts50 = 6.17 μg/mL), n-propyl gallate (IC50 = 2.31 μg/mL) and gallic acid (IC50 = 2.38 μg/50 = 1.64 μg/mL) showed better50 = 3.86 μg/mL) and n-propyl50 = 1.71 μg/mL). Hexane extract was most protective against lipid peroxidation (IC50 = 0.52 mg/mL). Maximum total antioxidant activity was shown by chloroform extract (5.11 m mol g flavonoids content. In conclusion, aqueous and all organic extracts of bark possess considerable free radical scavenging and antioxidant potential, but chloroform, ethyl acetate and hexane extracts are among the potent ones. These antioxidant activities most probably contribute to the therapeutic benefits of the traditional claims of -1 ascorbic acid equivalent). All the extracts showed variable magnitude of phenolic andTerminalia bellerica Roxb.Terminalia bellerica Roxb.. management of a number of clinical disorders in South East Asia. In view of better understanding of its pharmacological action, (hexane, ethyl acetate, chloroform and butanol) of with different antioxidant testing models, including 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'- azinobis-(3-ethylbenzothiazoline)-6-sulfonic acid (ABTS), antilipid peroxidation and total antioxidant capacity assays. Total phenolic and flavonoids content was also analyzed. Results showed that both chloroform (IC possess potent DPPH radical scavenging activity, which was even better than standard antioxidants (trolox (IC mL)). In ABTS decolorization assay ethyl acetate extract (IC potential than others fractions and standards such as trolox (IC gallate (IC